Clinical data analysis of 86 patients with invasive infections caused by Malassezia furfur from a tertiary medical center and 37 studies - Zhang, Xiaohui; Jin, Fei; Ni, Fang; Xu, Yuqiao; Lu, Yanfei; Xia, Wenying (Frontiers in Cellular and Infection Microbiology, 2023)
Objective Malassezia furfur (M. furfur) is a lipophilic, conditionally pathogenic yeast that mainly causes skin infections, but the reports of related invasive infections are increasing. The aim of this study is to provide clinical data to assist physicians in the management of patients with invasive infections caused by M. furfur. Methods A case of pulmonary infection caused by M. furfur in a hematopoietic stem cell transplant patient for aplastic anemia was reported. In addition, the literature on invasive infection by M. furfur published in PubMed and Web of Science in English until 31 July 2022 was reviewed. Results Clinical data analysis of 86 patients (from 37 studies and our case) revealed that most of them were preterm (44.2%), followed by adults (31.4%). M. furfur fungemia occurred in 79.1% of the 86 patients, and 45 of them were clearly obtained from catheter blood. Other patients developed catheter-related infections, pneumonia, peripheral thromboembolism, endocarditis, meningitis, peritonitis and disseminated infections. Thirty-eight preterm infants had underlying diseases such as very low birth weight and/or multiple organ hypoplasia. The remaining patients had compromised immunity or severe gastrointestinal diseases. 97.7% of patients underwent invasive procedures and 80.2% received total parenteral nutrition (TPN). Fever, thrombocytopenia and leukocytosis accounted for 55.8%, 38.4% and 24.4% of patients with M. furfur invasive infections, respectively. 69.8% of the patients received antifungal therapy, mainly amphotericin B (AmB) or azoles. Of 84 patients with indwelling catheters, 58.3% underwent the removal of catheters. TPN were discontinued in 30 of 69 patients. The all-cause mortality of 86 patients was 27.9%. Conclusions M. furfur can cause a variety of invasive infections. These patients mostly occur in premature infants, low immunity and severe gastrointestinal diseases. Indwelling catheters and TPN infusion are major risk factors. AmB, l-AmB and azoles are the most commonly used agents, and simultaneous removal of the catheter and termination of TPN infusion are important for the treatment of M. furfur invasive infections.